2017
DOI: 10.1177/1362361317698939
|View full text |Cite
|
Sign up to set email alerts
|

Support for adults with autism spectrum disorder without intellectual impairment: Systematic review

Abstract: Adults with autism spectrum disorder without intellectual impairment may benefit from a range of support services. This article presents the results of a systematic review assessing the effectiveness of supportive interventions for adults with autism spectrum disorder without intellectual impairment. A total of 32 studies were included; most focused on younger male participants. Although evidence was lacking for most types of intervention, employment programmes and social skills training were found to be effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 68 publications
(84 reference statements)
0
43
0
Order By: Relevance
“…This extreme shift is often referred to as the “service cliff” (Roux et al, 2015). Existing services for adults frequently only enroll those with more significant needs such as intellectual disability, psychiatric disorders, or medical problems (Lorenc et al, 2017). Individuals with autism spend significantly more time of life within the adult service system compared to the child system.…”
Section: Lesson 1: Apply Prevention and Early Intervention Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This extreme shift is often referred to as the “service cliff” (Roux et al, 2015). Existing services for adults frequently only enroll those with more significant needs such as intellectual disability, psychiatric disorders, or medical problems (Lorenc et al, 2017). Individuals with autism spend significantly more time of life within the adult service system compared to the child system.…”
Section: Lesson 1: Apply Prevention and Early Intervention Theoriesmentioning
confidence: 99%
“…The authors reported that meta-analyses could not be conducted due to the heterogeneity of intervention content, outcomes, and outcome measures. Even more concerning was that few studies used validated measurement tools (Lorenc et al, 2017). This same challenge of lack of consistency across outcomes and measurement tools has been reported in numerous review articles.…”
Section: Lesson 3: Attend To Outcomes and Measurement Toolsmentioning
confidence: 99%
“…Adults with autism spectrum disorder (ASD) who do not have an associated learning disability—so called ‘high functioning’ individuals (Lorenc et al 2016 )—are at risk of experiencing negative outcomes across a number of domains of life and to “function well below the potential implied by their normal range intellect” (Marriage et al 2009 ). Adults with high functioning autism spectrum disorder (HFASD) have been found to experience poor and comorbid physical and mental health issues (Mazurek and Kanne 2010 ; Hofvander et al 2009 ; Howlin and Moss 2012 ; Lake et al 2014 ; Lugnegård et al 2011 ; Mattila et al 2010 ; Gotham et al 2015 ); high unemployment, underemployment, and workplace discrimination (Baldwin and Costley 2016 ; Gotham et al 2015 ; Howlin and Moss 2012 ; Smith et al 2012 ; Taylor and Seltzer 2011 ; Lake et al 2014 ); limited meaningful social and romantic relationships (Baron-Cohen and Wheelwright 2003 ; Farley et al 2009 ; Jennes-Coussens et al 2006 ; Tobin et al 2014 ); and struggle to gain autonomy and independence in their lives (Renty and Roeyers 2006 ; Lake et al 2014 ; Howlin and Moss 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low-level support broadly concerns any non-intensive service aiming to provide general support, which is not directed at treating a clinical problem or deficit, to people in their everyday lives (Lorenc et al 2016 ). The focus of low-level support can be wide ranging and can be delivered through a variety of settings, such as health services, social care, the community, and telephone and internet based services (Lorenc et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation